If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + -1 + -9p + 5 = 0 Reorder the terms: -1 + 5 + 7p + -9p = 0 Combine like terms: -1 + 5 = 4 4 + 7p + -9p = 0 Combine like terms: 7p + -9p = -2p 4 + -2p = 0 Solving 4 + -2p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2p = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -2p = 0 + -4 -2p = 0 + -4 Combine like terms: 0 + -4 = -4 -2p = -4 Divide each side by '-2'. p = 2 Simplifying p = 2
| 0.25(3+A)=0.5 | | .5(2x-6)=2x | | 3-8x=27-12x | | 183+k-20=-15 | | 48-3m=5m | | 7m-5m-6= | | 7y-15x=9 | | 12p=7p+35 | | .25x+12=-.25x | | 6x-15=3x+12 | | 5y^4-7y^2+1.5=0 | | 7(x+1)-1=34 | | n-29-16=246 | | 6q+3-4q=9 | | t+(-3)=8 | | 9x-6y=8 | | t+3-3=8-3 | | a+8=12 | | .20x=7-.80x | | 3x+5=2x+9 | | 0.75+2(x-0.5)=3x-0.4 | | 16=.5x-8 | | -215+e+(-43)=-145 | | 34+p+112=78-7 | | -2(3u+x)+5(3x+u)= | | 17+38= | | 215+e+(-43)=-145 | | 3y+7=14 | | 5w+4z=-.7 | | 8-3(p-4)=2 | | -45=x+(-3)+50 | | -4r-2=6 |